Transient Expression of Whitefly Effectors in Nicotiana benthamiana Leaves Activates Systemic Immunity Against the Leaf Pathogen Pseudomonas syringae and Soil-Borne Pathogen Ralstonia solanacearum - Lee, Hae-Ran; Lee, Soohyun; Park, Seyeon; van Kleeff, Paula J. M.; Schuurink, Robert C.; Ryu, Choong-Min (Frontiers in Ecology and Evolution, 2018)
Infestation of plants with the phloem-feeding whitefly Bemisia tabaci modulates root microbiota and both local and systemic immunity against microbial pathogens. Specifically, aboveground whitefly infestation suppresses pathogen propagation and symptom development caused by the soil-borne pathogens Agrobacterium tumefaciens and Ralstonia solanacearum in the root system through systemic signal transduction. Therefore, we hypothesized that secreted protein(s)/non-protein factors from whitefly saliva (referred to as candidate effectors) might function as insect determinants that activate systemic acquired resistance (SAR) in the host plant. Here, we intensively screened a cDNA library constructed from mRNA from whitefly feeding on Nicotiana benthamiana leaves and selected three candidate effectors, 2G4, 2G5, and 6A10, that appear to reduce disease development caused by the aboveground pathogen Pseudomonas syringae pv. tabaci and the soil-borne pathogen R. solanacearum. Transient expression of the three candidate effector cDNAs in leaves primed the expression of SAR marker genes NbPR1a and NbPR2 in local and systemic leaves against P. syringae pv. tabaci, while leaf infiltration with 2G4 and 6A10 cDNA elicited strong defense priming of SAR markers following drench application of R. solanacearum on plant roots. In silico and qRT-PCR analyses revealed the presence of 2G5 and 6A10 transcripts in insect salivary glands. This is the first report of whitefly effectors that prime SAR against aboveground and belowground bacterial pathogens.